(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Psoriasis is one of the most common inflammatory autoimmune dermatologic diseases. The major concerns of psoriasis are social stigma which leaves a significant emotional impact for the patient. However, systematic management strategies, diet modification and timely monitoring shows an improvement in health-related quality of life and thus an improvement in social and psychological wellbeing. Severity of psoriasis tends to fluctuate with exogenous factors like diet, environmental factors etc. Spontaneous exacerbations and remissions are usual. There IS no specific treatment protocol in the management of psoriasis. In Ayurveda the symptoms are more similar to Vata kapha predominant Kushta, more specifically Sidhma kushta. The present study is aimed to treat a 22-year-old male patient, a known case of plaque psoriasis admitted in the IPD of Kayachikitsa department, Govt. Ayurveda College, Thiruvananthapuram. Deepana, Pachana Sodhana, Samana and Rasayana were the treatment protocol included. Ayurvedic approach in a single case of psoriasis is found beneficial in correcting the inherent Agnimandya at Koshta and Dhatu level and thus arrest the progression of the autoimmune inflammatory pathology. PASI (Psoriasis Assessment Severity Scale) score was used to assess the severity of lesions. Before treatment PASI score was 5.7 which reduced to 4.2 after 2 weeks. At the time of discharge PASI score was 0. The case report shows no recurrence of symptoms on review after 4 weeks.